2016
DOI: 10.18632/oncotarget.7300
|View full text |Cite
|
Sign up to set email alerts
|

ERβ decreases the invasiveness of triple-negative breast cancer cells by regulating mutant p53 oncogenic function

Abstract: Most (80%) of the triple-negative breast cancers (TNBCs) express mutant p53 proteins that acquire oncogenic activities including promoting metastasis. We previously showed that wild-type ERβ (ERβ1) impedes epithelial to mesenchymal transition (EMT) and decreases the invasiveness of TNBC cells. In the present study we searched for signaling pathways that ERβ1 uses to inhibit EMT and invasion in TNBC cells. We show that ERβ1 binds to and opposes the transcriptional activity of mutant p53 at the promoters of gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
59
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(64 citation statements)
references
References 55 publications
(87 reference statements)
3
59
0
1
Order By: Relevance
“…Knockdown of p63 reversed the effect of ERb1 on cell cycle of chemotherapy-treated NSCLC cells, indicating its involvement in the mechanism of ERb1 action. Moreover, we previously showed that ERb1 interacts with p63 to promote upregulation of p63 target genes in breast cancer cells (46). Among these, Cyclin G2 (CCNG2) is an estrogenregulated gene that is activated by p63 to control the G 2 -M cellcycle checkpoint (61,62).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Knockdown of p63 reversed the effect of ERb1 on cell cycle of chemotherapy-treated NSCLC cells, indicating its involvement in the mechanism of ERb1 action. Moreover, we previously showed that ERb1 interacts with p63 to promote upregulation of p63 target genes in breast cancer cells (46). Among these, Cyclin G2 (CCNG2) is an estrogenregulated gene that is activated by p63 to control the G 2 -M cellcycle checkpoint (61,62).…”
Section: Discussionmentioning
confidence: 99%
“…One of the mechanisms by which estrogen receptors elicit their tumor-associated functions involves their transcriptional cooperation with the p53-family proteins p53 and p63 (46,47). To further elucidate the molecular pathways that mediate the effect of ERb1 on chemotherapy response of NSCLC cells, we investigated whether ERb1 acts through p63 in H1299 cells.…”
Section: Erb1 Synergizes With P63 To Enhance the Chemosensitivity Of mentioning
confidence: 99%
See 1 more Smart Citation
“…Intriguingly, the ERβ isoform displays strong regulatory effects on EMT/MET factors and metastasis in breast cancer. ERβ expression was enough to induce E-cadherin expression in basal-like ERα-negative cells, suggesting anti-metastatic functions of the receptor in breast cancer 154 , 155 . Despite significant progress, the role of ERs in bone metastasis is still uncertain.…”
Section: Ers In Breast Cancermentioning
confidence: 96%
“…On the other hand, some studies discovered ERβ to be a better prognostic indicator in patients with breast cancer 51–53. Ström et al 51 showed that the growth of luminal T47D cells expressing mutant p53 was inhibited by ERβ, both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%